Training on Writing Independent Curriculum Teaching Modules Using the Canva Edu Application: Pelatihan Penulisan Modul Ajar Kurikulum Merdeka dengan Pemanfaatan Aplikasi Canva Edu - R., Syahrul; Atmazaki; Hayati, Yenni; Ningsih, Ayu Gustia; Indriyani, Vivi (Universitas Lancang Kuning, 2024)
The change in the curriculum in Indonesia from Curriculum 13 (K13) to the Independent Curriculum requires teachers to be ready to face these changes. Changes in learning tools are something that cannot be avoided by teachers as teachers. The learning plan (RPP) has been abandoned and moved to the Teaching Module. The presence of an independent curriculum not only provides changes to learning tools, but also to the competencies that teachers must have. Digital competence to produce interesting teaching modules has of course become an obligation, especially since the government has equipped teachers with the learn.id email. This email is integrated into the licensed Canva application, so teachers no longer have difficulty in designing teaching modules. It is hoped that the use of teaching modules using the Canva application will be able to answer the need for creating interesting teaching tools. A good teaching module does not only lie in its appearance, but also in its content. Writing teaching modules based on local wisdom will certainly make the teaching modules not only quality in terms of appearance, but also in terms of content. Based on the results of interviews with the head of the Subject Teachers' Conference (MGMP) of SMP Kota Pariaman, it is known that teachers are not yet skilled in designing teaching modules using Canva. Apart from that, the teaching modules that have been designed by teachers are not based on local wisdom. This background is what underlies the community service team of lecturers at the Indonesian and Regional Language and Literature Department to carry out training in writing teaching modules. The teaching module writing training that was carried out was attended by 20 Indonesian language subject teachers who are members of the Pariaman City Indonesian Language MGMP. The aim of this service is to provide knowledge and training to Pariaman City Indonesian Language MGMP teachers in using the Canva application in designing independent curriculum teaching modules. The training began with an explanation of the relationship between the use of technology in implementing the independent curriculum, then the material presented was the steps for using the licensed Canva application using a Belajar.id account. Teachers are guided to register. After registration, teachers go to their Canva account and start designing teaching modules. The teaching module designed by the teacher does not contain differentiated learning, therefore the training continues with conveying the essence of differentiated learning. Strategy in writing teaching modules by paying attention to differentiated learning. The training ended with teaching module material containing local wisdom. Teachers design teaching modules based on the independent curriculum which contains local wisdom in the form of guided assignments. Making teaching modules using the Canva application described previously. The training methods used were question and answer, direct practice and demonstration, and evaluation was carried out through distributing questionnaires before and after the training. The results of the questionnaire analysis showed that in general participants were satisfied with the training schedule and time, as well as the topics presented. Even though some participants experienced difficulties due to inadequate internet connections and devices, there were indications that the participants succeeded in increasing their knowledge and motivation in using the Canva application through the Belajar.id account. Apart from that, the teaching modules produced by teachers are also good and interesting.